Translating Geographic Works as a Means to Consolidate the Idea of Nation. The Case of the Section on Colombia in Elisée Reclus’ Nouvelle Géographie Universelle - López, Daniel (Íkala, Revista de Lenguaje y Cultura, 2018)
This article is based on a dissertation for a master's degree in Hispanic studies. It deals with the translation into Spanish of the section about Colombia from the Nouvelle géographie universelle by the French geographer Élisée Reclus. This translation, titled Colombia, was made by the Colombian geographer Francisco Javier Vergara y Velasco, just after the publication of the original in 1893. This study aims to restore the protagonists and the stakes involved in this translation process in their historic context, in a time when illusions of national unity of the nascent American countries were manifested, for example, in focusing on geographic works. The figure of the geographer-translator is here considered more as a subject that has left its mark, especially as a geographer in this translation-rewriting, than just a bridge between languages.